Patterns of longevity and fecundity at two temperatures in a set of heat-selected recombinant inbred lines of Drosophila melanogaster - Sambucetti, Pablo Daniel (2015)
Quantitative trait loci (QTL) were mapped for longevity and fecundity at two temperatures, 20 and 30 °C, in two sets of recombinant inbred lines (RIL) highly differing in thermotolerance. Early fecundity (EF) and longevity showed a negative association between temperatures. For instance, longevity was higher and fecundity was lower in the RIL panel showing higher life span at 30 °C. One X-linked QTL (7B3-12E) co-localized for longevity and EF at 20 °C, with one QTL allele showing a positive additive effect on longevity and a negative effect on EF. The across-RIL genetic correlation between longevity and EF was not significant within each temperature, and most QTL that affect life span have no effect on EF at each temperature. EF and longevity can mostly be genetically uncoupled in the thermotolerance-divergent RIL within each temperature as opposed to between temperatures. QTL were mostly temperature specific, although some trait-specific QTL showed possible antagonistic effects between temperatures.